螺旋流血液ポンプのモーター改良による差圧流量推定精度の向上 - 斎藤, 逸郎; 圦本, 晃海; 原, 伸太郎; 村上, 遥; 磯山, 隆; 阿部, 裕輔; 李, 欣陽; 羽合, 佳範 (Transactions of Japanese Society for Medical and Biological Engineering, 2016)
Sensor less estimation of pressure and pump flow has been an important subject for developing artificial hearts. However, estimated values are often incorrect influenced by the change in blood viscosity that changes with various factors. Therefore, viscosity estimation is essential for accurate estimation of pressure and flow. In previous study, we proposed viscosity estimation with table estimation method and in vitro study was performed using helical flow pump. However, dispersion was found with nonlinear characteristic of motor. In this study, we tried to improve viscosity estimation with modification of motor having linear characteristics. As a result, standard deviations of estimated viscosity reduced from 0.51 to 0.20. Consequently, dispersion of estimated pressure and flow could be reduced.